EFEKTIVITAS SISTEM INFORMASI ASN TERINTEGRASI SUMEDANG (SIPANTES) PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN SUMEDANG - Nurwan, Teddy Marliady; Zahra, Laila; Hendrayan, Thalisa Revina (JRPA - Journal of Regional Public Administration, 2024)
This study aims to determine the effectiveness of Sumedang Integrated ASN Information System (SIPANTES) in the Personnel and Human Resource Development Agency of Sumedang Regency. It is an information system built to meet the needs of personnel management in effective and efficient local government. The research method used is descriptive research using the qualitative analysis study approach. As for the data collection techniques used are librarianship studies and field studies (observation, interviews and documentation studies). Data analysis techniques use Sugiyono theory, data reduction, data display and conclusion drwing/verification. Informants in this study were determined using the purposive sampling method, which is 4 people. From the results of this study, SIPANTES in BKPSDM of Sumedang Regency has not reached the desired level of effectiveness. The main obstacles related to the management of personnel data that are still manual and the complexity of adding features to SIPANTES, which gave rise to complaints from some SKPD. To increase effectiveness, it is necessary to optimize the preparation for changes and the use of SIPANTES, with careful planning, involving all relevant parties, as well as the implementation of more intensive socialization and education. Thus, the positive potential of SIPANTES can be optimized to support more efficient personnel management in Sumedang Regency.